Evaluation of different electrodes in electrocoagulation-flotation process for Chlorella vulgaris harvesting - Wahyu Diski Pratama; Hadiyanto Hadiyanto (Case Studies in Chemical and Environmental Engineering)
This study investigated ten electrode materials for electrocoagulation-flotation (ECF) of Chlorella vulgaris. Magnesium showed the highest separation efficiency (98.7 %), followed by aluminum (97.34 %), iron (94.42 %), copper (93.17 %), zinc (91.65 %), nickel (91.50 %), lead (90.31 %), titanium (87.14 %), brass (84.92 %), and stainless steel (78.8 %). ECF increased the pH of the medium from 8.48 to the highest 10.89 by the brass electrode. Separated medium from all electrode materials after the ECF process can be recycled for further microalgae cultivation, which could economize water resources and reduce costs. This study underscores the ECF's efficacy for efficient and sustainable biomass recovery, especially using magnesium electrodes.